Analysis of a model of teamwork by Hill - Konstantin Petkovski; Fanche Joshevska (UTMS Journal of Economics, 2014)
The contemporary management of the intellectual capital of an organization, as a major determinant for efficient and effective operation of the organization has access to the teamwork. Teamwork means quality leadership which is necessary for a successful team management. In the theory and the practice are given a number of models for teamwork and team leadership, however, in this case the subject of this paperwork will be the analyzing of the model of team leadership according to Hill. According to this model there are two functions of team leading established: leading functions in the team and leading functions out of the team. In the first part, which refers to the functions of leadership in the team, are set two major categories: team leader's tasks and the built relationships and atmosphere in the team. In terms of the functions of the leader out of the team, the model focuses on two categories, namely: the functions of leadership out of the team, but within the organization and leading functions of the team outside the organization.
Keywords: D23; 330; team; leadership; teamwork; efficiency and effectiveness